Preparation and characterization of porous TiO2 thin films by sol-gel method for Extremely Thin Absorber-ETA solar cell applications - Hosseini, A.; İcli, K. C; Güllü, H. H. (My University, 2013)
Nanoporous TiO2 thin films have been widely used as window and n-type material for the Extremely Thin Absorber-ETA solar cells. Nano scale titanium dioxide (TiO2) films were deposited on the surfaces of bare glass and Indium Tin Oxide (ITO) coated glass substrates using spin coating method. The effect of different spinning rates on the surface structures and properties of the films was investigated. The surface morphology of nanostructure TiO2-coated films were characterized by Atomic Force Microscopy (AFM), Scanning Electron Microcopy (SEM), X-ray Diffraction (XRD) and BET studies. UV-Vis spectroscopy and dark I-V measurement were also performed to get the information about the optical and electrical properties. The test results proved that; by changing the spinning rates homogeneous anatase films of TiO2 with different thicknesses can be produced. The investigation show that TiO2 porous films obtained by spin coating method with 8000 rpm-spinning rate have the appropriate properties for ETA solar cell study

Nano-gözenekli TiO2 ince filmleri, Çok İnce Soğurucu - ETA güneş gözeleri için pencere katmanı ve n-tipi malzeme olarak yaygın bir şekilde kullanılmaktadır. Nano boyutlu titanyum dioksit (TiO2) filmleri işlenmemiş cam ve indiyum kalay oksit (ITO) kaplı cam alttaş yüzeylerine döndürerek kaplama (spin coating) yöntemi kullanılarak büyütülmüştür. Farklı döndürme hızlarının yüzey yapıları ve ince filmlerin özellikleri üzerine etkileri incelenmiştir. Nano-yapıda TiO2 kaplı filmlerin yüzey morfolojisi Atomik Kuvvet Mikroskopu (AFM), Taramalı Elektron Mikroskopu (SEM), X-Işını Kırınımı (XRD) ve BET çalışmaları ile karakterize edilmiştir. Ayrıca, UV-Vis spektroskopi ve karanlık I-V ölçümleri optik ve elektriksel özellikler hakkında bilgi edinmek için gerçekleştirilmiştir. Deneme sonuçları, döndürme hızlarını değiştirerek farklı kalınlıklarda homojen anataz TiO2 ince filmlerinin üretilebildiğini göstermektedir. Araştırmalar 8000 rpm döndürme hızı ile döndürerek kaplama metodu ile elde edilen gözenekli TiO2 filmlerin ETA güneş gözeleri çalışması için uygun özellikler taşıdığını göstermektedi
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Thin film; TiO2; Spin coating; XRD; Band gap; Transmittance; İnce Film; Döndürerek Kaplama; Bant aralığı; Geçirgenlik